3D printing in Healthcare. Issue 1 (January 2017) - Hornick, John
John Hornick is a partner based in the Washington, DC, USA, headquarters of the Finnegan IP law firm, one of the largest IP firms in the world. Based on his more than 30 years of experience, Hornick counsels clients on virtually every aspect of IP law. He founded Finnegan's 3D Printing Working Group and advises and educates clients about 3D printing and the IP issues of this rapidly developing and potentially disruptive technology, and how it may affect their businesses. He is the author of the award-winning book, 3D Printing Will Rock the World. The only IP attorney selected by the National Academies to participate in the US Comptroller General Forum on Additive Manufacturing (which was the basis of a report to the US Congress), and a juror for the International Additive Manufacturing Award, Hornick has been widely published and frequently speaks on 3D printing and its potential effects on IP law and the world.